65 When a metabolic screening fails a potential treatable diagnosis. (22nd November 2019) - Elkhateeb, Nour; McSweeney, Melanie; Grunewald, Stephanie
Abstract : Background: Congenital defects of glycosylation (CDGs) are a rapidly enlarging heterogenous group of metabolic conditions (more than 130 to date), presenting usually with multisystem manifestations. Serum transferrin isoelectric focusing (IEF) is the gold standard for screening, yet it has its limitations. SLC35A2-CDG is a rare type of CDG, caused by mutations in the X-linked SLC35A2 gene encoding the UDP-galactose transporter. It has multisystem manifestations, with predominant neurological involvement. It is a potentially treatable disorder by oral galactose supplementation. Diagnosis is challenging as IEF is normal in most patients. Patient and methods: We are reporting the clinical, biochemical, radiological and genetic data of six recently diagnosed patients with SLC35A2-CDG. Results: 5/6 patients were females. Age of diagnosis ranged between 5 and 17 years. Clinical presentations included; 6/6 developmental delay, 5/6 epileptic encephalopathy, 6/6 hypotonia, 4/6 growth failure, 3/6 dysmorphism, 5/6 neuroimaging abnormalities, 5/6 skeletal abnormalities. The phenotype in the male case was different from the 5 female cases, with milder course of seizures but pronounced skeletal abnormalities and growth failure. Serum transferrin test was abnormal in 1/4, normal in 3/4, not performed in 2/4. Whole exome sequencing revealed de novo mutations in 6/6, with 2/6 somatic mosaicism. 4/6 patients were started on oral galactose (1.5 g/kg/day), duration of treatment ranged between (4 -16 months), with favourable response in 4/4. Discussion: Our data support previous reports on SLC35A2-CDG, confirming that the main features are developmental delay, intractable seizures, abnormal neuroimaging and hypotonia. Diagnosis is usually delayed due to clinical manifestations being nonspecific. Serum transferrin testing is not a reliable diagnostic modality. WES is usually required for diagnosis. Conclusions: SLC35A2-CDG is a rare X-linked CDG affecting the UDP-galactose transporter. Diagnosis is very challenging, due to nonspecific manifestations and CDG screening being negative in most patients. Early diagnosis is essential for timely galactose supplementation.